2007
DOI: 10.1038/sj.mt.6300165
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Safe Herpes Simplex Virus Type 1 Amplicon Vector for Transcriptionally Targeted Therapy of Human Hepatocellular Carcinomas

Abstract: Our previous studies have shown that transgene expression could be targeted to proliferating cells when cell cycle transcriptional regulatory elements were incorporated into herpes simplex virus type 1 (HSV-1) amplicon backbone vectors. In the study reported here, we further demonstrated the transcriptional activation of transgene expression in association with the onset of cellular proliferation using the mouse partial hepatectomy model. Moreover, transcriptional regulation could be rendered specific to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…[197][198][199] For example, transcriptional regulation can be rendered specific to human hepatocellular carcinoma cells by inserting the chimeric gene Gal4/NF-YA under the regulation of a HCC-specific hybrid promoter. 200 Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been shown to induce apoptosis in neoplastic cells. It has been reported the efficacy of amplicon delivered TRAIL and its secreted form (S-TRAIL) in treating tumors in vivo and in monitoring both gene delivery and efficacy of TRAIL-mediated apoptosis by dualsubstrate bioluminescence imaging.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…[197][198][199] For example, transcriptional regulation can be rendered specific to human hepatocellular carcinoma cells by inserting the chimeric gene Gal4/NF-YA under the regulation of a HCC-specific hybrid promoter. 200 Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been shown to induce apoptosis in neoplastic cells. It has been reported the efficacy of amplicon delivered TRAIL and its secreted form (S-TRAIL) in treating tumors in vivo and in monitoring both gene delivery and efficacy of TRAIL-mediated apoptosis by dualsubstrate bioluminescence imaging.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…A key issue in developing a safe and effective oncolytic virotherapy is the achievement of maximal killing of tumor cells while maintaining tumor specificity of viral targeting (13)(14)(15). We have recently shown that a replication-defective HSV-1 helper virus (CgalΔ3), lacking the essential ICP4 gene, became oncolytic in a tissue type-specific fashion when the ICP4 gene was provided by an amplicon expressing this gene under the regulation of a prostate-specific promoter, ARR 2 PB (16).…”
mentioning
confidence: 99%
“…Furthermore, because the HSV-1 amplicon viral vectors can be packaged in the absence of helper virus, and they typically contain only two noncoding elements of the HSV, ori s and pac, these vectors are therefore relatively noncytotoxic and nonpathogenic when administered in vivo. 24 We have independently confirmed this by injecting the amplicon viral vectors (1Â10 6 transduction units, TU) into immunocompetent BALB/c mice via the tail vein. 25 Thus, the HSV-1 amplicon vectors should serve well as potential carrier of therapeutic genes to HCC tumors.…”
Section: Introductionmentioning
confidence: 78%